2007
DOI: 10.1038/nm1679
|View full text |Cite
|
Sign up to set email alerts
|

Cross-presentation of caspase-cleaved apoptotic self antigens in HIV infection

Abstract: We found that the proteome of apoptotic T cells includes prominent fragments of cellular proteins generated by caspases and that a high proportion of distinct T cell epitopes in these fragments is recognized by CD8+ T cells during HIV infection. The frequencies of effector CD8+ T cells that are specific for apoptosis-dependent epitopes correlate with the frequency of circulating apoptotic CD4+ T cells in HIV-1-infected individuals. We propose that these self-reactive effector CD8+ T cells may contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 49 publications
4
120
1
Order By: Relevance
“…It has been shown that autoantigens can be generated by the collaborative efforts of activated caspases and proteasome, which may result in lymphodepletion in HIV-infected patients (33). Of note, various tumor cells express basal levels of caspase activities (23) or they transiently activate effector caspases without cell death (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that autoantigens can be generated by the collaborative efforts of activated caspases and proteasome, which may result in lymphodepletion in HIV-infected patients (33). Of note, various tumor cells express basal levels of caspase activities (23) or they transiently activate effector caspases without cell death (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, comprehensive proteomic studies of human islets demonstrate that these 'housekeeping genes' are, without exception, expressed in islet cells [19,20]. In conjunction with the shared predominance of executioner caspases 3 and 8 during apoptosis induction in both cell types [18,21], we reasoned that similar peptide fragments are probably generated under apoptotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The caspase-cleaved apoptotic self-antigens used in this study have been reported previously by Rawson et al and were generated by apoptosis induction in HLA-A2-restricted, human CD95 + CD8 + T cell clones by treatment with a monoclonal antibody to CD95 [18]. The apoptotic cells were lysed and their proteome was compared to control cells using subtractive analysis by two-dimensional electrophoresis to identify modified proteins.…”
Section: Experimental Approach For the Analysis Of Apoptosis-associatmentioning
confidence: 99%
See 2 more Smart Citations